(untitled) (Tikrit Journal of Veterinary Science, 2024)
This study aimed to describe the anatomical and histological parameters in the spleen of the wild rabbits. Ten healthy adult wild rabbits were included. The spleen was collected and prepared for histological and morphological studies. The spleen of wild rabbit is dark red color and locate in abdominal cavity beneath the diaphragm. The histological study showed that the wild rabbit spleen has thick capsule, covered the white and red pulps.